Cyclic Failure of a Cr–Au Bilayer on Polyimide: In Situ Transmission Electron Microscopy Observations of Interfacial Dislocation Mechanisms - Gebhart, David D.; Krapf, Anna; Schretter, Lukas; Lassnig, Alice; Merle, Benoit; Cordill, Megan J.; Gammer, Christoph (Advanced Engineering Materials, 2024)
This work presents in situ transmission electron microscopy observations of dislocation activities and associated fatigue properties in a cross-sectional sample of a Cr–Au bilayer on a polyimide substrate under cyclic loading. Dislocation structures in the Au layer are observed to evolve into a geometrically necessary boundary parallel to the Cr–Au interface, which significantly impedes dislocation motion and plays a crucial role in enhancing the fatigue resistance of the studied sample. While a comparison to the damage in a conventional blanket film testing geometry reveals some differences in the accumulation of plastic flow, the findings can provide insights into the underlying mechanisms governing fatigue in nanostructured multilayer materials on polymer substrates.
CRIS-Team Scopus Importer:2024-05-03
Keywords: cyclic loading; dislocation activities; fatigue resistance; geometrically necessary boundaries; in situ transmission electron microscopy; metal bilayer; polyimide substrates